Seleção e desenvolvimento de adjuvantes para uso em imunizações com proteínas recombinantes de Plasmodium - Bargieri, Daniel Youssef [UNIFESP] (2009)
The C-terminal region of Plasmodium merozoite surface protein 1 (MSP119) is being studied as one of the main targets for the development of a vaccine against malaria. Several studies have shown high imunogenicity of this region in experimental immunizations when injected in the presence of strong adjuvant formulations. In the present study we evaluate the possibility of using recombinant proteins based on the sequence of MSP119 to immunize mice by a mucosal route. Also, we generate new recombinant proteins consisting in the genetic fusion of the MSP119 to the flagellin FliC (flagellar protein of Salmonella enterica Typhimurium), to increase the immunogenicity of the antigen. Initially, we evaluated the capacity of the molecules cholera toxin (CT), heat-labile E. coli enterotixin (LT) or CpG ODN 1826, to act as adjuvants in mucosal intranasal immunization of mice with the recombinant proteins His6PvMSP119 or His6PvMSP119-PADRE (containing the universal T helper epitope PADRE). When administered in the presence of CT or LT, both recombinant proteins were highly immunogenic by the intranasal route. CpG ODN 1826 was less efficient as adjuvant by this route. The addition of CpG ODN 1826 in CT adjuvanted immunizations increased the specific IgG2c titers. These results showed that CT and LT are potent mucosal adjuvants in immunizations with recombinant malaria antigens and that CpG ODN 1826 can, in this case, be used as a tool to modulate the pattern of the immune response. Subsequently, we expressed a recombinant protein consisting of the sequence of PvMSP119-PADRE genetically fused to FliC (His6FliC-PvMSP119- PADRE). We showed that this fusion protein preserved the antigenic properties of PvMSP119 and the ability of flagellin to activate TLR5. The immunization of mice using this recombinant fusion protein induced high titers of specific antibodies and the presence of antigen-specific IFN-g producing cells in the spleen. The addition of CpG ODN 1826 in the vaccine formulations modulated the immune response by augmenting the specific titers of IgG2c. In addition, sera from immunized mice recognized the parasite in indirect immunofluorescence assay (IFA). Our results provided a new class of malaria vaccine formulation with intrinsic adjuvant property capable of stimulating specific humoral and cellular immune responses when administered alone or in the presence of other adjuvants. Finally, we expressed a recombinant protein containing the sequence of Plamodium falciparum MSP119 (PfMSP119) fused to FliC (His6FliC-PfMSP119). This fusion protein retained the capacity of flagellin to activate TLR5. Immunization of mice with the His6FliC-PfMSP119 alone induced high titers of specific antibodies and IFN-g producing cells. The addition of adjuvants such as CpG ODN 1826 or Quil-A (saponin of Quillaja saponaria) increased the levels of IgG2c and the cellular immune response, measured by the IFN-g secretion by immune spleen cells in culture. In addition, sera from immunized rabbits recognized the parasites in IFA and inhibited parasite growth in vitro. These results provide evidences that the fusion of malaria antigens to flagellin is an inexpensive and viable alternative for the development of a malaria vaccine.